(untitled) (diségno, 2018)
“Conventionally, of course, drawing is an active process which leaves a trail of carbon on the paper. With a computer sketch, however, any line segment is straight and can be relocated by moving one or both of its end points.” [Sutherland 1963, p. 102]. With these surprisingly laconic words, the twenty-five-year-old Ivan Sutherland described, in his doctoral thesis [1], the most obvious difference between a traditional drawing and an electronic graphic document. Creator of the first interactive design system to be made public, called Sketchpad, presented precisely in the abovementioned thesis, and the first man to have drawn luminous lines on a monitor, he posed questions that have not yet been fully resolved even today, more than fifty years after that earliest act. Is it possible, in fact, to call this new iconic artifact with the same name by which an object drawn by hand has been defined? Sutherland answered in the abovementioned chapter that he had significantly entitled Drawing vs. moving: “[…] there is no state of the system that can be called ‘drawing’”.